Genomic footprints of repeated evolution of CAM photosynthesis in a Neotropical species radiation. (25th August 2020) - De La Harpe, Marylaure; Paris, Margot; Hess, Jaqueline; Barfuss, Michael Harald Johannes; Serrano‐Serrano, Martha Liliana; Ghatak, Arindam; Chaturvedi, Palak; Weckwerth, Wolfram; Till, Walter; Salamin, Nicolas; Wai, Ching Man; Ming, Ray; et al.
Abstract: The adaptive radiation of Bromeliaceae (pineapple family) is one of the most diverse among Neotropical flowering plants. Diversification in this group was facilitated by shifts in several adaptive traits or "key innovations" including the transition from C3 to CAM photosynthesis associated with xeric (heat/drought) adaptation. We used phylogenomic approaches, complemented by differential gene expression (RNA‐seq) and targeted metabolite profiling, to address the mechanisms of C3 /CAM evolution in the extremely species‐rich bromeliad genus, Tillandsia, and related taxa. Evolutionary analyses of whole‐genome sequencing and RNA‐seq data suggest that evolution of CAM is associated with coincident changes to different pathways mediating xeric adaptation in this group. At the molecular level, C3 /CAM shifts were accompanied by gene expansion of XAP5 CIRCADIAN TIMEKEEPER homologs, a regulator involved in sugar‐ and light‐dependent regulation of growth and development. Our analyses also support the re‐programming of abscisic acid‐related gene expression via differential expression of ABF2/ABF3 transcription factor homologs, and adaptive sequence evolution of an ENO2/LOS2 enolase homolog, effectively tying carbohydrate flux to abscisic acid‐mediated abiotic stress response. By pinpointing different regulators of overlapping molecular responses, our results suggest plausible mechanistic explanations for the repeated evolution of correlated adaptive traits seen in a textbook example of an adaptive radiation. Abstract : In this study, we address key aspects of the evolutionary drivers of repeated shifts between C3 /CAM photosynthesis, a complex adaptation in response to xeric habitats. We survey genomic, transcriptomic and metabolic changes in the extremely species‐rich bromeliad genus, Tillandsia, and related taxa.